Impact of obesity on day‐night differences in cardiac metabolism. Issue 3 (4th March 2021) - Mia, Sobuj; Sonkar, Ravi; Williams, Lamario; Latimer, Mary N.; Frayne Robillard, Isabelle; Diwan, Abhinav; Frank, Stuart J.; Des Rosiers, Christine; Young, Martin E.
Abstract: An intrinsic property of the heart is an ability to rapidly and coordinately adjust flux through metabolic pathways in response to physiologic stimuli (termed metabolic flexibility). Cardiac metabolism also fluctuates across the 24‐hours day, in association with diurnal sleep‐wake and fasting‐feeding cycles. Although loss of metabolic flexibility has been proposed to play a causal role in the pathogenesis of cardiac disease, it is currently unknown whether day‐night variations in cardiac metabolism are altered during disease states. Here, we tested the hypothesis that diet‐induced obesity disrupts cardiac "diurnal metabolic flexibility", which is normalized by time‐of‐day‐restricted feeding. Chronic high fat feeding (20‐wk)‐induced obesity in mice, abolished diurnal rhythms in whole body metabolic flexibility, and increased markers of adverse cardiac remodeling (hypertrophy, fibrosis, and steatosis). RNAseq analysis revealed that 24‐hours rhythms in the cardiac transcriptome were dramatically altered during obesity; only 22% of rhythmic transcripts in control hearts were unaffected by obesity. However, day‐night differences in cardiac substrate oxidation were essentially identical in control and high fat fed mice. In contrast, day‐night differences in both cardiac triglyceride synthesis and lipidome were abolished during obesity. Next, a subset of obese mice (induced by 18‐wks ad libitum high fat feeding) were allowed access to the high fat diet only during the 12‐hours dark (active) phase, for a 2‐wk period. Dark phase restricted feeding partially restored whole body metabolic flexibility, as well as day‐night differences in cardiac triglyceride synthesis and lipidome. Moreover, this intervention partially reversed adverse cardiac remodeling in obese mice. Collectively, these studies reveal diurnal metabolic inflexibility of the heart during obesity specifically for nonoxidative lipid metabolism (but not for substrate oxidation), and that restricting food intake to the active period partially reverses obesity‐induced cardiac lipid metabolism abnormalities and adverse remodeling of the heart.